Monetary policy operations and the financial system - Bindseil, Ulrich (Oxford : Oxford University Press, 2014)
The book first introduces the subject by explaining monetary policy operations in normal times, including the key instruments (open market operations, standing facilities, reserve requirements, and the collateral framework). Second, the book reviews the basic mechanics of financial crises as they have hit economies many times. The book then explains what central banks need to do to when financial markets and banks are impaired to fulfil their monetary policy and financial stability mandates. Besides demonstrating the need for non-conventional monetary policy measures, the book also highlights their dangers, such as moral hazard and increased central bank risk taking. The book draws a number of lessons from the crisis on non-conventional monetary policy operations, assessing what measures have worked well, and how a framework should be designed in future normal times such as to contribute to make financial crises less likely.
Includes bibliographical references (pages 299-313) and index.
oif 06/12/2017
Loans
Keywords: Monetary policy; Banks and banking, Central; Financial institutions, International